Modified state space procedures for pseudodynamic testing. - Wang, Yen-Po (Earthquake engineering & structural dynamics.)
The existing on-line numerical integration algorithm are derived from the Newmark method, which is based on an approximation of derivatives in the differential equation. The state space procedure (SSP), based on an interpolation of the discrete excitation signals for piecewise convulation integral, has been confirmed as more reliable than the Newmark method in terms of numerical accuracy and stability. In an attempt to enhance the pseudodynamic test, this study presents an on-line integration algorithm (referred to as the OS-SSP method) via an integration of the state space procedure with Nakashima's operator splitting concept. Numerical stability and accuracy assessment of the proposed algorithm in addition to the explicit Newmark method and the OS method were investigated via an eigenvalue, SSP method is demonstrated as the most accurate method with an acceptable stability (although not unconditionally stable) characteristic. Therefore, the OS-SSP method is the most desirable method for pseudodynamic testing if the numerical stability criterion.